Endophytic Fungi in Rice Plants and Their Prospective Uses - Yingping Hu; Guodong Lu; Dongmei Lin; Hailin Luo; Mediatrice Hatungimana; Bin Liu; Zhanxi Lin (Microbiology Research, 2024)
In a long-term evolution, fungal endophytes have formed a mutually beneficial relationship with host plants. Therefore, what roles do fungal endophytes play in the growth and development of rice, one of the major food crops in the world, and agricultural production? This mini-review aims to highlight the diversity, identification, colonization, function, and mechanism of action of endophytic fungi isolated from rice tissues through a literature review; comprehensively expound the interaction mechanism between rice fungal endophytes and their hosts in stimulating the growth of rice plants and alleviating biological and abiotic stresses on plants; and contribute new ideas for rice production and a sustainable rice industry. Additionally, rice fungal endophytes, as a new resource, have broad prospects in the development of biopesticides, biocontrol agents, and new medicine.